The procedure of recourse do the II section of Sygnature Apostolic - LESZCZYŃSKI, GRZEGORZ (Prawo Kanoniczne, 2014)
In accord with the can. 221 § 1 of Code of Canon Law the Christian faithful can legitimately vindicate and defend the rights which they enjoy in the Church before a competent ecclesiastical court in accord with the norm of law. In this article the author is trying to explane the main norms of the the procedure of recourse do the II section of Sygnature Apostolic.